2013
DOI: 10.1007/s00264-013-2225-6
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral decompression using a unilateral pedicle construct for lumbar stenosis

Abstract: Bilateral decompression via a unilateral approach using unilateral pedicle screw fixation for two-level lumbar stenosis with instability, which can maintain the lumbar lordosis and the disc space height, is an effective and less invasive method than with bilateral constructs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…anterior or posterior), types of surgery (minimally invasive or open), types of graft (allograft and/or autograph), and cages used (yes or no). Information regarding the clinical care pathway after surgery was described in only six [53,[56][57][58][59]65] out of twenty-five studies.…”
Section: Selected Studiesmentioning
confidence: 99%
“…anterior or posterior), types of surgery (minimally invasive or open), types of graft (allograft and/or autograph), and cages used (yes or no). Information regarding the clinical care pathway after surgery was described in only six [53,[56][57][58][59]65] out of twenty-five studies.…”
Section: Selected Studiesmentioning
confidence: 99%
“…Alternative surgical approaches such as stand-alone ALIF [42] or different screw entry points such as cortical screw-rod fixation [43] would completely avoid affection of the medial and intermediate branch nerves. Other studies showed that iatrogenic alterations decrease postoperative cross-sectional area (CSA) and contractile tissue density of back muscles [20,44,45].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, attening of the sagittal lumbar curvature happened in 7 cases (63.6%). Other studies demonstrated that attened spines are often associated with degeneration of multiple discs and back muscle weakness, which further signi cantly decreases spinal exibility and stability [25,26,27] .…”
Section: Discussionmentioning
confidence: 99%